The role of local leadership in community- based rural homestay in Malaysia - Abas, Siti Aisah; Abd Halim, Norhazliza (Readers Insight Publisher, 2018)
This conceptual research intended to highlight the emergent concept of local leadership in Community-Based Rural Homestay (CBRH) in Malaysia. In addition, the development and progress of local participation in CBRH also become the focal point to be discussed. Undeniably, Community-Based Rural Homestay become a vehichle and development for local community to enhance their socioeconomy through engagement as homestay operators. Ministry of Tourism and Culture put a lot effort to improve infrastructure and facilities in every homestay providers to boost up tourist arrival. Apart of being source of income to local community, CBRH also offers various local product, quality rural experience and culture preservation and conservation for tourist. Thus, CBRH programme has proved as a platform for local community empowerment and distributed benefir as individual or collective basis. Most of the homestay operator motivated to participate in this programme due to value-added to their source of income and medium for them to promote their local culture to tourist. However, incompetent leaders to lead the CBRH initiatives become a challenge to homestay operator as they need a proactive leaders to drive and facilitate them in order to handle tourist and homestay operation.